Shaping ability of rotary or reciprocating systems for oval root canal preparation: a micro-computed tomography study - Espir, Camila Galletti [UNESP] (2018)
Objectives: To evaluate the shaping ability and cleaning after oval root canal preparation using one or more instruments in reciprocating or rotary motion. Materials and methods: Oval-shaped mandibular incisors were selected, based on the radiographic diameter (2 ≤ diameter ratio ≤ 4), and assigned according to root canal preparation (n = 18): single-file (Reciproc R40); two reciprocating files (Unicone size 20 and 40, .06 taper) or Mtwo rotary files until a size 40, .06 taper instrument. Root canal preparations were performed using an open root canal model. Scanning was performed before and after preparation using SkyScan 1176 with a voxel size of 17.42 μm. Volume, percentage of debris, and percentage of uninstrumented surface were analyzed in the entire root canal and in each root canal third. Data were compared using ANOVA and Tukey or Kruskal-Wallis and Dunn tests (α = 5%). Results: The initial volume were similar among the groups (p > .05). Unicone preparation was associated with higher debris, increase in root canal volume and uninstrumented surface in entire root canal and in the middle third (P < .05). Mtwo was associated with lower uninstrumented surface in the entire root canal and in the cervical third. The apical third were similar for the three preparations. Conclusions: Unicone system using two instruments in reciprocating motion resulted in higher increase in volume. However, less remaining debris was observed when Reciproc single-file and Mtwo rotary systems were used. Clinical relevance: A preparation that volumetrically increases the root canal is not necessarily associated with better cleaning. Shaping and hard-tissue debris removal depends on root canal anatomy, kinematics, number of instruments, and instrument design.